2000
DOI: 10.1139/z00-092
|View full text |Cite
|
Sign up to set email alerts
|

Determining food requirements in marine top predators: a comparison of three independent techniques in Great Cormorants,Phalacrocorax carbocarbo

Abstract: Assessment of food requirements is a key feature in the evaluation of the ecological status of the marine megafauna. However, this remains technically difficult because prey intake by marine top predators occurs mainly under water, out of sight. In this paper, we compare three independent methods currently available for use in quantitative dietary studies: (1) time-energy budget; (2) stomach-temperature measurements; and (3) automatic weighing. To this end, concurrent measurements were performed on Great Cormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Evans et al, 1988;Gardner et al, 2002). As with leopard sharks, a rise in gastric pH with meal ingestion, followed by a decrease to baseline levels, has been observed for birds (Duke et al, 1975;Peters, 1997a;Gremillet et al, 2000) and humans (James, 1957;Gardner et al, 2002). Humans continuously secrete acid, with an unstimulated (i.e.…”
Section: Gastric Ph Changesmentioning
confidence: 95%
See 3 more Smart Citations
“…Evans et al, 1988;Gardner et al, 2002). As with leopard sharks, a rise in gastric pH with meal ingestion, followed by a decrease to baseline levels, has been observed for birds (Duke et al, 1975;Peters, 1997a;Gremillet et al, 2000) and humans (James, 1957;Gardner et al, 2002). Humans continuously secrete acid, with an unstimulated (i.e.…”
Section: Gastric Ph Changesmentioning
confidence: 95%
“…Gastric pH has been measured continuously for snakes (Secor, 2003), birds (Peters 1997a,b;Gremillet et al, 2000), ruminants (Enemark et al, 2003) and humans (e.g. Evans et al, 1988;Gardner et al, 2002).…”
Section: Gastric Ph Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary and behavioral information of cormorants migrating through Michigan and for resident non-breeders (subadults and nonbreeding adults) are generally lacking (Gremillet et al 2000). A review by Wires et al (2001) found that population estimates for non-breeders ranged from one to four non-breeders for each breeding pair.…”
Section: Dietmentioning
confidence: 99%